2003
DOI: 10.1063/1.1604934
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of negative and positive charges in Ge+ ion implanted silicon dioxide layers subjected to high-field electron injection

Abstract: Negative and positive charge trapping in a constant current regime under high-field electron injection both from Al electrode and Si substrate in high-dose Ge+ ion implanted and then rapid thermal annealed thin-film dioxide has been studied. Negatively charged traps as well as generated positive charges with effective capture cross sections of σ1(−)>10−14 cm2, σ2(−)≈1.8×10−15, σ3(−)≈2×10−16, and σ4(−)≈3×10−18 cm2, as well as σ1(+)≈(5–7)×10−15 and σ2(+)≈3.3×10−16 cm2, respectively, are shown to be introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
(25 reference statements)
3
21
0
Order By: Relevance
“…Assuming that the charge traps are located in the middle of the dioxide the data obtained from the C OX DV CC vs. Q INJ curves correlate well with a shift of the C-V characteristics (not shown). Such a kind of specific charging was not observed in the previous studies of other types of ionimplanted oxides [3,6], and can be linked to the presence of specific amphoteric defects with capture cross-sections distributed in the range of 8 Â 10 À17 -5 Â 10 À18 cm 2 . We suggest that these defects are associated with disturbed ARTICLE IN PRESS Fig.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Assuming that the charge traps are located in the middle of the dioxide the data obtained from the C OX DV CC vs. Q INJ curves correlate well with a shift of the C-V characteristics (not shown). Such a kind of specific charging was not observed in the previous studies of other types of ionimplanted oxides [3,6], and can be linked to the presence of specific amphoteric defects with capture cross-sections distributed in the range of 8 Â 10 À17 -5 Â 10 À18 cm 2 . We suggest that these defects are associated with disturbed ARTICLE IN PRESS Fig.…”
Section: Resultsmentioning
confidence: 48%
“…Another series of samples with a Tb concentration of 1.5% was annealed in the temperature range of 800-1100 1C for 60 min. For the sake of comparison, some experiments were performed on samples incorporating a SiO 2 layer implanted with Ge ions to a concentration of up to 3% and heat treated by rapid thermal annealing (RTA) at 1000 1C for 6 s [3]. A semi-transparent indium-tin oxide (ITO) layer of 100 nm thickness was then deposited to fabricate electrodes with different diameters (from 0.1 to 0.5 mm).…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11] It has been reported that ion implantation of Ge into thin SiO 2 layers on Si wafers, followed by annealing, results in Ge accumulation at the Si/ SiO 2 interface. [12][13][14] Diffusion of Ge atoms during annealing can alter the interface, thereby having a significant influence on the memory characteristics of such structures. [13][14][15] It has also been suggested that charge storage is more likely to occur within the NCs rather than at the NC/ SiO 2 interface.…”
Section: J H Han and Chungwoo Kimmentioning
confidence: 99%
“…[12][13][14] Diffusion of Ge atoms during annealing can alter the interface, thereby having a significant influence on the memory characteristics of such structures. [13][14][15] It has also been suggested that charge storage is more likely to occur within the NCs rather than at the NC/ SiO 2 interface. 16 These reports suggest that the memory effect should depend strongly on the concentration and the position of defects and/or Ge NCs.…”
Section: J H Han and Chungwoo Kimmentioning
confidence: 99%
“…Critical issues of the MOSLED performance are the device durability in terms of device operating lifetime, which has to be improved, and the strong-field injection-associated oxide degradation, which has to be prevented or at least retarded [11][12][13].…”
Section: Introductionmentioning
confidence: 99%